Using a template to improve the accuracy and efficiency of the Jebsen–Taylor Hand Function Test: A comparative study. (March 2014) - Harte, Daniel; Curran, Denise; Hamill, Philip; Porter-Armstrong, Alison; Wilson, Lynn
Introduction: The Jebsen–Taylor Hand Function Test is a standardised assessment that relies upon precise test administration through the placement of a number of small items in each subset. This set up has been criticised in the literature as being time consuming and open to non-precision error in item placement. This study investigates whether application of a novel template board to the testing procedure of the Jebsen–Taylor Hand Function Test enhances accuracy and reduces the clinical time taken to administer the test when compared to non-template-based testing practices. Methods: The template board was marked to highlight where each test item should precisely be located during subtest administration. Additionally, three therapists completed 10 timed trials each in test preparation and setting up subtests 2, 3, 6 and 7 with and without the template to assess efficiency. Results: Results show that set up without using a template resulted in an average total of 10% accuracy in subtest 2, 0% accuracy in subtest 3 and 3.33% accuracy in subtests 6 and 7. The acceptable value on these tests to demonstrate accuracy is 100% ( p < 0.05). The results also demonstrate that the total time to complete test set up was significantly less when using the template board ( p < 0.05). Discussion: This study demonstrates the difficulty in achieving accuracy without a template board and the associated inefficiencies. The availability of standardised assessments that are easy to use in clinical practice and that have sound reliability, validity and responsiveness is necessary to objectively and accurately measure hand function.